Efektivitas Akupresur Berbasis Pemberdayaan Keluarga terhadap Penurunan Tekanan Darah Sistolik dan Diastolik pada Pasien Hipertensi di Wilayah Kerja Puskesmas Kecamatan Pasar Minggu - Emi Yuliza; Solehudin Solehudin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Hypertension is a major public health problem associated with an increased risk of cardiovascular disease, stroke, kidney disease, and other complications. The 2023 Indonesian Health Survey reported that the prevalence of hypertension based on blood pressure measurements among adults aged ≥18 years was 30.8%. Hypertension management requires a sustainable approach that includes not only pharmacological treatment but also behavioral modification and family empowerment. Acupressure is a complementary intervention that may contribute to blood pressure control. This study aimed to analyze the effectiveness of family empowerment-based acupressure in reducing blood pressure among patients with hypertension in the working area of Pasar Minggu District Public Health Center. A pre-experimental one-group pretest-posttest design was used. The study involved 12 patients with hypertension who received family empowerment-based acupressure intervention. Systolic and diastolic blood pressure were measured before and after the intervention. Descriptive and inferential analyses were performed using a paired t-test for systolic blood pressure and the Wilcoxon signed-rank test for diastolic blood pressure, with a significance level of α=0.05. The mean systolic blood pressure decreased from 146.67±28.31 mmHg before intervention to 126.83±14.06 mmHg after intervention, representing a mean reduction of 19.83 mmHg. The paired t-test demonstrated a statistically significant difference in systolic blood pressure (p=0.006). The mean diastolic blood pressure decreased from 90.25±17.47 mmHg to 82.42±8.43 mmHg, with a mean reduction of 7.83 mmHg. However, the change in diastolic blood pressure was not statistically significant (p=0.241, Wilcoxon test). Family empowerment-based acupressure showed potential for reducing blood pressure, particularly systolic blood pressure, among patients with hypertension. This approach may be considered as a complementary intervention in family nursing; however, larger studies with control groups are needed to establish stronger evidence of effectiveness.